The Literary Chronotope Forms in the Poetry of Erkin Vahidov - Zamira BALTAEVA (Genius Journals, 2022)
This article deals with the poems on historical, social, cultural, and educational topics written by Erkin Vahidov, one of the most prominent figures in Uzbek poetry of the twentieth century. There is a discussion about the forms of the literary chronotope or the unity of time and spatial features, the poetic integrity of the solution to a specific goal, its transformation into philosophical and aesthetic values, the factors that create imagery. The poetic integrity of the solution to a specific goal, its transformation into philosophical and aesthetic values, the factors that create imagery. So, the literary chronotope is not only in prose works. It is naturally clarified that it is equally relevant to poetic works as well.
Keywords: Image; Criteria; Thinking; Philosophy